Language, Epistemology, and Mysticism - Katz, Steven T. (2020)
This paper was originally published as a chapter in the book Mysticism and Philosophical Analysis, edited by Steven T. Katz and published by Oxford University Press in 1978. The text deals with epistemological issues of mysticism and problematizes some conceptions of this theme, its aim is especially to mark a way of approaching the data provided by mystics, focusing especially on the attempt to defend the conception as such as ideas are mediated by cultural, social, and religious contexts, mystical experiences are experienced,  as the author prefers to say, interpreted, in different ways according to these same contexts.